Enzymatic response and antibiotic resistance gene regulation by microbial fuel cells to resist sulfamethoxazole. (June 2023) - Chen, Ping; Jiang, Jiwei; Zhang, Shixuan; Wang, Xinyu; Guo, Xiaoyan; Li, Fengxiang
Abstract: Microbial fuel cells (MFCs) are a promising and sustainable technology which can generate electricity and treat antibiotic wastewater simultaneously. However, the antibiotic resistance genes (ARGs) induced by antibiotics in MFCs increase risks to ecosystems and human health. In this study, the activities of enzymes and regulation genes related to ARGs in MFCs spiked with sulfamethoxazole (SMX) were evaluated to explore the induction mechanism of ARGs. Under lower doses of SMX (10 mg/L and 20 mg/L SMX in this study), microorganisms tend to up regulate catalase and RpoS regulon to induce sul1, sul3 and intI1 . The microorganisms exposed to higher doses of SMX (30 mg/L and 40 mg/L SMX in this study) tend to up regulate superoxide dismutase and SOS response to generate sul2 and sulA . Moreover, the exposure concentrations of SMX had no significant effect on the electricity production of MFCs. This work suggested that the ARGs in MFCs might be inhibited by affecting enzymatic activities and regulatory genes according to the antibiotic concentration without affecting the electricity production. Graphical abstract: Image 1 Highlights: Microbial enzyme activity is different at different sulfamethoxazole concentrations. RpoS regulon was mainly induced at low concentrations of sulfamethoxazole. SOS response was mainly induced at high concentrations of sulfamethoxazole. Different concentrations of sulfamethoxazole can induce different resistance genes. Sulfamethoxazole affects microbial electricity generation and microbial activity.